RETRACTED: Stochastic scheduling of power system in the presence of electric vehicle and renewable sources considering security and economic indexes using an improved mutation particle swarm optimization (M-PSO) algorithm - Chang, Rui; Yan Xu; Fars, Ashk (International journal of hydrogen energy, 2023)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/policies/article-withdrawal). This article has been retracted at the request of <the Editor-in-Chief. Post-publication, the editor discovered suspicious changes in authorship between the original submission and the revised version of this paper. In summary, the paper was submitted by a sole author Ashk Fars. During revision, the authors Rui Chang (New Corresponding and First Author) and Yan Xu were added to the revised paper without explanation and without exceptional approval by the journal editor, which is contrary to the journal policy on changes to authorship. In addition, it appears that Ashk Fars was claiming an affiliation with Arian Company, Yerevan, Armenia. When questioned, the author was unable to provide convincing evidence of the existence and nature of this company. Overall, the editor feels that the findings of the manuscript cannot be relied upon and that the article needs to be retracted.>